2016
DOI: 10.1155/2016/1430641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Permeability and Mechanical Characteristics of Lignite

Abstract: Underground in situ pyrolysis and gasification is an important method to enable clean utilization of lignite in China. In this study, using the high-temperature triaxial permeability test equipment for different ranges of temperature and pore pressure, the permeability and mechanical characteristics of lignite from the Pingzhuang Mine Area in Chifeng have been examined. The results show that, at constant confining pressure, the elastic modulus of lignite decreases with increasing temperature. For temperature u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…To sum up, the mechanical parameters of the coal indicate a weakening trend with an increase in temperature, which is consistent with the research results of Xu et al [19] and Shao et al [20].…”
Section: Influence Of Temperature On the Mechanical Properties Of Dee...supporting
confidence: 91%
“…To sum up, the mechanical parameters of the coal indicate a weakening trend with an increase in temperature, which is consistent with the research results of Xu et al [19] and Shao et al [20].…”
Section: Influence Of Temperature On the Mechanical Properties Of Dee...supporting
confidence: 91%
“…This behavior was also observed in the literature, where, according to Ifelebuego and Momoh [29], who studied the sorption capacity of coconut residues with vegetable oil and diesel oil, this parameter decreased with increasing temperature. According SHAO et al [30], this is due to the reduction of permeability that occours with materials when the temperature rises. This increase generates the dilatation of the sorbent medium and reduces the porous volume of the material, reducing the permeable channels and, consequently, the surface area of oil adsorption and absorption.…”
Section: Sorbent Materials T (Min) T (°C) S (G/g) -Average Standard Dementioning
confidence: 99%
“…32,33 Taiyuan University of Technology studied the physical characteristics of coal during pyrolysis under high-temperature triaxial stress using an in situ developed high-temperature and high-pressure rock triaxial testing machine, 34 and the porosity of coal decreased with increasing pore pressure under in situ underground pyrolysis. 35,36 Duan et al 37 used a high-temperature and highpressure rheometer to study the pyrolysis characteristics of coal under different stress conditions. The results showed that the gas and semicoke yields increased with increasing stress, while the tar yield decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Research on in situ underground pyrolysis of coal is still in the laboratory stage. The University of Utah has studied the pyrolysis behavior of coal in the underground environment using chemical permeation devolatilization (CPD) model simulations and a high-pressure reactor. , The results indicate that the product of subsurface coal thermal treatment technology is mainly light crude oil. , Taiyuan University of Technology studied the physical characteristics of coal during pyrolysis under high-temperature triaxial stress using an in situ developed high-temperature and high-pressure rock triaxial testing machine, and the porosity of coal decreased with increasing pore pressure under in situ underground pyrolysis. , Duan et al used a high-temperature and high-pressure rheometer to study the pyrolysis characteristics of coal under different stress conditions. The results showed that the gas and semicoke yields increased with increasing stress, while the tar yield decreased.…”
Section: Introductionmentioning
confidence: 99%